2009
DOI: 10.1007/s00424-009-0668-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term regulation of vacuolar H+-ATPase by angiotensin II in proximal tubule cells

Abstract: Long-term effects of angiotensin II (Ang II) on vacuolar H(+)-ATPase were studied in a SV40-transformed cell line derived from rat proximal tubules (IRPTC). Using pH(i) measurements with the fluorescent dye BCECF, the hormone increased Na(+)-independent pH recovery rate from an NH(4)Cl pulse from 0.066 +/- 0.014 pH U/min (n = 7) to 0.14 +/- 0.021 pH U/min (n = 13; p < 0.05) in 10 h Ang II (10(-9) M)-treated cells. The increased activity of H(+)-ATPase did not involve changes in mRNA or protein abundance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 42 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…The renin- and/or Ang II-dependent activation of MAP kinases ERK1/2 appears to have been well established. Ang II also appears to stimulate V-ATPase activity in rat proximal tubule cells via mechanisms involving tyrosine kinase, p38 MAPK, and PI3K [31]. Since PRR is structurally identical to CAPER protein (endoplasmic reticulum-localized type 1 transmembrane adaptor precursor) and vacuolar H + -ATPase (V-ATPase), intracellular PRR may also mediate the intracellular actions of prorenin or renin [1,57,198].…”
Section: Overview Of the Prorenin/prr/map Kinases Erk 1/2 Axis In mentioning
confidence: 99%
“…The renin- and/or Ang II-dependent activation of MAP kinases ERK1/2 appears to have been well established. Ang II also appears to stimulate V-ATPase activity in rat proximal tubule cells via mechanisms involving tyrosine kinase, p38 MAPK, and PI3K [31]. Since PRR is structurally identical to CAPER protein (endoplasmic reticulum-localized type 1 transmembrane adaptor precursor) and vacuolar H + -ATPase (V-ATPase), intracellular PRR may also mediate the intracellular actions of prorenin or renin [1,57,198].…”
Section: Overview Of the Prorenin/prr/map Kinases Erk 1/2 Axis In mentioning
confidence: 99%
“…The B2 subunit is ubiquitously expressed, and it may be responsible for the translocation of V-ATPase from the cytosol to the membrane. Carraro-Lacroix et al demonstrated that immortalized rat proximal tubular cells exposed to angiontensin II exhibited an upregulation of V-ATPase activity that was partially caused by increased B2 cell surface expression; the B2 subunit contains an F-actin binding site, which interacts with actin filaments and allows trafficking to the cell surface 27 . The B2 subunit was upregulated in V-ATPase B1 subunit-deficient mice to compensate for the lack of B1, which was sufficient to maintain basal acid-base homeostasis, despite the downregulation of other V-ATPase subunits in the animal model 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In the in vitro perfused rabbit proximal tubule, the mechanism of the stimulation involved both apical Na + /H + exchange and basolateral Na + -base transport (236). Angiotensin II increased the Vmax of apical Na + /H + exchange and at higher concentrations also increased H + -ATPase activity in a proximal tubule OKP cell line by enhancing plasma membrane expression involving signaling through tyrosine kinase, PI3K, and P38 (140, 603). Angiotensin II has also been reported to increase apical H + -ATPase membrane vesicle insertion in rat proximal tubule fragments (727).…”
Section: Regulation Of Proximal Tubule H+/base Transporters and Wholementioning
confidence: 97%